Compte-rendu de lecture de : The EU and Africa from Eurafrique to Afro-Europa, edited by Adekeye Adebajo and Kaye Whiteman, Johannesburg, Wits University Press, 2012, 531 pp. ISBN: 978-1- 84904-171-3 - (:unkn) unknown (My University, 2013)
Compte-rendu de lecture de The EU and Africa from Eurafrique to Afro-Europa , edited by Adekeye Adebajo and Kaye Whiteman, Johannesburg, Wits University Press, 2012, 531 pp. ISBN: 978-1-84904-171-3
Keywords: African Research